Ameloblastoma: a retrospective single institute study of 34 subjects. (2nd January 2019) - Kelppe, Jetta; Hagström, Jaana; Sorsa, Timo; Suominen, Anna Liisa; Apajalahti, Satu; Haglund, Caj; Thorén, Hanna
Abstract: Objective: This study aims to clarify demographic and clinical aspects of patients with ameloblastoma treated at a single Finnish institute during 1985–2016. Associations between predictor variables (gender and age) and outcome variables (location, tumour type, growth patterns and average tumour size) were sought. Materials and methods: A retrospective cohort study was designed and implemented including 34 patients diagnosed with primary ameloblastoma and treated at the Helsinki University Central Hospital. Patient records were investigated, and tissue samples re-evaluated. The chi-square test was used on all categorized variables and t -test for continuous ones. A p value equal to or under .05 was considered significant. Results: Males were slightly more predominant among the Finnish patients with ameloblastoma. Maxillary tumours were seen exclusively in male patients ( p = .034). Additionally, these patients were older than patients with mandibular tumours ( p = .007). A mixture in histological growth patterns was more common than originally anticipated. The study revealed a wide range of clinical signs and subjective symptoms, of which pain or other sensations were experienced most often. Conclusions: This study of 34 subjects shows that southern Finnish patients with ameloblastoma do not substantially differ from patients in similar study designs.